Indicadores de produção dos grupos de pesquisa do Ins- Tituto Federal de Educação, Ciência e Tecnologia da Paraíba. - Perucchi., Valmira (2010)
Paraíba Federal Institute of Technology, Science, and Education IFPB is a part of the Brazilian educational system which has the scientific and technological development as its final activity. It offers technological and professional education in different modalities of teaching and intends to carry out applied research having its human resources organized in groups in order to develop research activities and reinforce knowledge. This research that presents the production indicators of these groups registered at the board of the National Council of Technological and Scientific Development CNPq, and qualified by the IFPB originates from the question: does the IFPB know of the production of its research groups? This questioning takes us to the objective: to get to know the scientific production and the technological results achieved by the research groups. This theme is relevant to the Information Science CI as an area that studies the dynamics of generation, collection, organization, storage, retrieval, interpretation, transmission, transformation, and utilization of information and the relation between information and knowledge leading to studies about technological and scientific production. The object of study is the 24 research groups of the IFPB created by the teaching staff s demands from 1994 onward and named according to the Knowledge Area Table of the Higher Education Staff s Assessment Coordination Capes. The data was manually collected from the résumés that are available at the Lattes Platform from 1994 to 2008 and are displayed by groups classified from 1 to 24 followed by the formation year. The analysis was carried out via the quantitative aspects of the production, dissemination and use of the registered information and applied to production assessment, subdivided into two periods, 1994/2000 and 2001/2008, and by the groups with 10 or more human resources and groups with 5 or less ones. In numerical terms, the groups technological and scientific production presents meaningful indicators with a significant involvement of the students; with the total number of 2.140 journal publications and 536 magazine articles. These media are the most used to disseminate scientific knowledge and technological results. There is 32 software, 5 technological products, and 13 processes or techniques without registration or patent. The groups research projects presented 6 cancelled ones, 106 finished, and 108 in progress. The groups, when developing projects, managed to get partnership and funding from renowned agencies which prove the relevance of the developed projects. We conclude that the production presented meaningful indicators, a result of research development with subsequent publication of the results and that it does not necessarily mean that the quantity of human resources has any direct relation with the production. These indicators justify the activities of the research groups to the IFPB formulate, follow and assess the research policies so that strategies are implemented aiming at a renewal of the researches, the expansion of the quantity of the research groups, and also enabling students and technicians participation as well as motivating the funding by the public aid agencies.